Learning Action Cells as Educational Technology: Enhancing Retention via Social Learning - Omerah Barangai; Renato Base (Language, Literature and Education: Research Updates Vol. 4, 2025)
This study examines the efficacy of Learning Action Cells (LACs) as a social learning-driven educational technology to address teacher retention and professional growth in the Bangsamoro Autonomous Region of Muslim Mindanao (BARMM), focusing on the Madamba School District. Grounded in Albert Bandura’s Social Learning Theory (SLT), LACs are structured as peer-driven collaborative platforms that foster resilience among educators in a region marked by geographic isolation, socio-cultural diversity, and systemic neglect. Using a total enumeration approach, the study included all 107 teachers across 13 schools in the Madamba School District, integrating quantitative metrics—such as an 83.50% retention rate among active participants (vs. 0% among non-participants), mean professional growth scores (4.296–4.361), and validated survey instruments (Cronbach’s \(α\) = 0.89)—with qualitative insights from teacher narratives (e.g., “LACs make me want to stay”). Total enumeration ensured comprehensive coverage of the teacher population, eliminating sampling bias and aligning with studies emphasising its advantages over partial sampling in small, defined populations. Findings reveal that LACs mitigate attrition by enhancing teacher agency, adaptability, and community integration, aligning with UNESCO’s benchmarks for effective professional development. The study underscores LACs’ scalability as a low-cost, high-impact model for fragile contexts, offering actionable insights for policymakers to institutionalise collaborative frameworks that bridge theory, practice, and cultural responsiveness in underserved educational systems.